PAWS1 controls Wnt signalling through association with casein kinase 1α. (7th March 2018) - Bozatzi, Polyxeni; Dingwell, Kevin S; Wu, Kevin ZL; Cooper, Fay; Cummins, Timothy D; Hutchinson, Luke D; Vogt, Janis; Wood, Nicola T; Macartney, Thomas J; Varghese, Joby; Gourlay, Robert; Campbell, David G; et al.
Abstract: The BMP and Wnt signalling pathways determine axis specification during embryonic development. Our previous work has shown that PAWS1 (also known as FAM83G) interacts with SMAD1 and modulates BMP signalling. Here, surprisingly, we show that overexpression of PAWS1 in Xenopus embryos activates Wnt signalling and causes complete axis duplication. Consistent with these observations in Xenopus, Wnt signalling is diminished in U2OS osteosarcoma cells lacking PAWS1, while BMP signalling is unaffected. We show that PAWS1 interacts and co‐localises with the α isoform of casein kinase 1 (CK1), and that PAWS1 mutations incapable of binding CK1 fail both to activate Wnt signalling and to elicit axis duplication in Xenopus embryos. Synopsis: PAWS1 is a novel mediator of the Wnt signalling pathway through its interaction with and regulation of CK1α. Microinjection of PAWS1 mRNA into Xenopus embryos causes complete axis duplication through the activation of Wnt signalling. PAWS1‐knock‐out U2OS osteosarcoma cells exhibit diminished Wnt signalling, which can be rescued by the restoration of PAWS1. PAWS1 interacts and co‐localizes with Ser/Thr protein kinase CK1α and the PAWS1 mutants incapable of binding CK1α fail to induce axis duplication and activate Wnt signalling. The PAWS1:CK1α complex appears to control nuclear translocation of β‐catenin upon Wnt stimulation. Abstract : PAWS1 is a novel mediator of the Wnt signalling pathway through its interaction with and regulation of CK1α.